Területi egyensúly: A munkaerőpiac és az ingatlanárak kapcsolata Magyarországon; Spatial equilibrium: Links between the labor market and housing prices in Hungary - Békés Gábor; Bisztray Márta (Hungarian Academy of Sciences, Institute of Economics, 2019)
– The aim of this paper is to investigate how the spatial equilibrium model applies to Hungary. For this we create a new database on modified micro-regional level between 2001 and 2014 with real estate/property market, labor market, regional and demographical data. We use this database to answer the question: how strong is the relationship between the real estate/property market and the labor market? We find that regarding changes the connection is quite weak and unstable, the spatial equilibrium model is not working properly. One reason for that is the difference in patterns we can see across different temporal or spatial sub-samples. Before the financial crisis the most important variable changing in accordance with house prices was the rate of people working at local firms. But after the crisis in-migration and other demographic processes become more important. We also see a difference between the Eastern and the Western part of the country not only in levels but also in the relation between house prices and other local factors.
Keywords: R30; R31; 330; spatial equilibrium; housing market; local labor market